Praktik Hutang Piutang Online pada Aplikasi Pinjaman Now Tinjauan Fatwa DSN MUI dan KHES - Annisa Firdausi Nuzula; Ahmad Junaidi; Luqman Hakim; Mahatir Muhamad Ihsan (Fakultas Syariah Institut Agama Islam Negeri Ponorogo, 2022)
Qardh is a property that is lent or given by (the creditor) to someone in need (the debtor), intended to help the debtor, and he must return it with the same value and time that both parties have determined. There are several ways to carry out accounts payable, one of which is by using online media or online applications. The legality of an online loan is also required to have a permit and be registered with the Financial Services Authority (OJK). The